2023
DOI: 10.3390/molecules28093802
|View full text |Cite
|
Sign up to set email alerts
|

Essential and Potentially Toxic Elements (PTEs) Content in European Tea (Camellia sinensis) Leaves: Risk Assessment for Consumers

Abstract: Tea (Camellia sinensis) is the second most consumed beverage worldwide, playing a key role in the human diet. Tea is considered a healthy drink, as its consumption has been linked to a lower risk of cardiovascular disease-related events and death, stroke, metabolic syndrome and obesity. However, several studies have shown that C. sinensis is a hyperaccumulator of Al and other elements that are considered potentially toxic. In the present study, the contents of 15 elements (both essential and toxic) were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…Very recently, we conducted a study on the content of 15 elements (both potentially toxic and essential) in tea leaves collected from the same tea gardens reported here and found that there was no risk from the consumption of European teas for consumers in terms of potentially toxic elements [ 37 ]. This present investigation now builds on to this existing information regarding the characterization of European teas in terms of potential health benefits as assessed through their antioxidant profile, polyphenol content and metal chelating activity in both the more popular hot water brews and in the upcoming popularity of cold water brews.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, we conducted a study on the content of 15 elements (both potentially toxic and essential) in tea leaves collected from the same tea gardens reported here and found that there was no risk from the consumption of European teas for consumers in terms of potentially toxic elements [ 37 ]. This present investigation now builds on to this existing information regarding the characterization of European teas in terms of potential health benefits as assessed through their antioxidant profile, polyphenol content and metal chelating activity in both the more popular hot water brews and in the upcoming popularity of cold water brews.…”
Section: Discussionmentioning
confidence: 99%
“…The honey safety was evaluated by comparing the concentrations obtained with the legal values that set limits for this contaminant in the honey matrix. Additionally, the potential non−carcinogenic health risk associated with element exposure through consumption was estimated based on the hazard quotient (HQ) measured by comparing the average daily intake dose (ADD) to the corresponding daily intake reference dose (RfD) (Equation (1) and (2)) [ 44 ]: where C (mg kg −1 ) is the mean concentration of the Hg in honey, IR is the average honey consumption (2.7 g person −1 day −1 ) [ 45 ], BW is the average body weight of an adult (70 kg), and RfD (mg kg −1 day −1 ) is the daily intake reference dose suggested by World Health Organization (Joint FAO/WHO Expert Committee on Food Additives) [ 23 ]. An HQ of less than 1 shows no significant risk of non−carcinogenic effects on consumers.…”
Section: Methodsmentioning
confidence: 99%
“…Teas are categorized into three main types according to the production process. A distinction is made between non-fermented green tea, semi-fermented oolong tea and fully fermented black tea [ 4 , 5 ]. In addition to these main types, there are others such as white, yellow and pu-erh.…”
Section: Introductionmentioning
confidence: 99%